2004
DOI: 10.1152/japplphysiol.00403.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal stress on the vestibulosympathetic reflexes in humans

Abstract: Wilson, Thad E., and Chester A. Ray Effect of thermal stress on the vestibulosympathetic reflexes in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Slight increases in cerebral blood velocity during cold stress are observed, and these increases are maintained during heat-up tilt (15, 31). Alterations in orthostatic tolerance and cerebral blood flow due to thermal stress appear to be independent of the gain of other neural-induced postural reflexes (13, 33) but rather, in part, are related to previously alluded-to alterations in cardiac function and mechanics.…”
Section: Implication For Orthostatic Tolerancementioning
confidence: 96%
“…Slight increases in cerebral blood velocity during cold stress are observed, and these increases are maintained during heat-up tilt (15, 31). Alterations in orthostatic tolerance and cerebral blood flow due to thermal stress appear to be independent of the gain of other neural-induced postural reflexes (13, 33) but rather, in part, are related to previously alluded-to alterations in cardiac function and mechanics.…”
Section: Implication For Orthostatic Tolerancementioning
confidence: 96%
“…Their study showed that high thermal stress may affect the autonomic equilibrium of ruminant organisms by inducing the sympathetic nervous system nonlinearly. Wilson and Ray, [27] reported that whole-body heating raised heart rate, internal temperature, and muscle sympathetic nerve activity but mean arterial blood pressure was unaffected.…”
Section: Effect Of Thermal Stress On Autonomic Nervous Systemmentioning
confidence: 99%
“…For example, figure 1 shows the MSNA tracing of a subject and it can be appreciated that the waveform is mostly noisy and needs to be oriented on the background of the timing of R waves in order to provide meaningful interpretations. Several parameters have been used to quantify MSNA, namely the number of bursts per minute (burst frequency), the number of bursts per 100 heart beats (burst incidence), burst amplitude distribution, area under the bursts, arbitrary units and fractal dimension (Yamada et al 1989, Naughton et al 1998, Macefield et al 1999, Sverrisdottir et al 2000, Fadel et al 2004, Kimmerly et al 2004, Wilson and Ray 2004.…”
Section: Introductionmentioning
confidence: 99%